Inhibition of Cdk5 rejuvenates inhibitory circuits and restores experience-dependent plasticity in adult visual cortex. (January 2018) - Li, Yue; Wang, Laijian; Zhang, Xinxin; Huang, Mengyao; Li, Sitong; Wang, Xinxing; Chen, Lin; Jiang, Bin; Yang, Yupeng
Abstract: Cyclin-dependent kinase 5 (Cdk5) acts as an essential modulator for neural development and neurological disorders. Here we show that Cdk5 plays a pivotal role in modulating GABAergic signaling and the maturation of visual system. In adult mouse primary visual cortex, Cdk5 formed complex with the GABA synthetic enzyme glutamate decarboxylase GAD67, but not with GAD65. In addition to enhancement in the surface level of NR2B-containing NMDA receptors, inhibition of Cdk5 reduced the protein levels of GADs and Otx2, while leaving intact the expression of vesicular GABA transporter and subunits of GABAA or AMPA receptors. Whole-cell patch-clamp recording in layer II/III pyramidal neurons revealed a decrease in the frequency of miniature inhibitory postsynaptic current (mIPSC). Consequently, pharmacological inhibition and genetic knockdown of Cdk5 in adult mice led to a restoration of juvenile-like ocular dominance plasticity in vivo and long-term synaptic potential in layer II/III induced by white matter stimulation in vitro . Interestingly, we did not observe an alteration of perineuronal nets of extracellular matrix, but a reinstatement of the capability to evoke long-term depression at inhibitory synapses (iLTD), which depended on presynaptic endocannabinoid receptors and was a sign of the rejuvenated GABAergic synapses. Enhancement of GABA signaling by diazepam impeded ocular dominance plasticity rescued by Cdk5 inhibition. These results thus suggest that a physiological role of Cdk5 in visual cortex is to consolidate and stabilize neural circuits through controlling GABAergic signaling. Highlights: Cdk5 inhibition reduces GAD expression and mIPSC frequency in adult visual cortex. Pharmacological inhibition of Cdk5 enhances long-term synaptic plasticity. Cdk5 blockade reinstates the capability to evoke endocannabinoid-mediated iLTD. Suppression of Cdk5 restores experience-dependent visual plasticity in adulthood. Enhancing GABA signaling by diazepam impedes the restoration of visual plasticity.